Combining Soil Nail and Vetiver Grass In A Slope Protection Project In Vietnam - N. T. Nghia; L. G. Lam; T. Hino (Lowland Technology International, 2019)
This paper presents a combination of soil nail and vetiver grass for slope protection in a project in center of Vietnam. The application of vetiver grass is considered as a green environmental solution for erosion surface control while soil nail with shotcrete is a traditional method for steep slope stabilization. The shotcrete surface of soil nail system will be replaced by vetiver grass for the combination of soil nail and vetiver grass. This is not only economic solution but also meets requirement for landscaping. This paper presents design and construction techniques and compares the construction cost with tradiional soil nail methods.